Five new species of Limacodidae (Lepidoptera: Zygaenoidea) from South-East Asia - Solovyev, Alexey V.; Saldaitis, Aidas (Zootaxa, 2021)
The species Iragoides dudai sp. nov. from China (Sichuan), Euphlyctina butvilai sp. nov. from China (Zhejiang and Yunnan), Sansarea alenae sp. nov. from China (Yunnan), Narosoideus witti sp. nov. from China (Sichuan, Yunnan, Shaanxi, and Jiangxi), Griseothosea mousta sp. nov. from China (Yunnan), Thailand (Chiang Mai, Nan and Chiang Dao), and Laos (Luang Namtha and Luang Prabang) are described as new to science. The taxonomical status of dark and pale forms of Iragoides crispa (Swinhoe, 1890) is discussed.